2013
DOI: 10.1093/icvts/ivt379
|View full text |Cite
|
Sign up to set email alerts
|

Apicoaortic conduit and cerebral perfusion in mixed aortic valve disease: a computational analysis

Abstract: The computational analysis suggested a protective effect, rather than steal phenomenon, of the apicoaortic conduit towards the cerebral perfusion, even in cases of mixed aortic valve disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…More recently, Fragomeni et al used computational flow analysis to evaluate the systemic hemodynamic changes determined by a second outlet between the heart and the great vessels (i.e., from AVB), even in the context of mixed aortic valve disease. 17 The authors concluded that even under conditions of moderate AI, ''. The remaining antegrade flow (through the native aortic valve) after [AVB] supports, almost exclusively, cerebral perfusion, whereas the remaining body vessels perfuse by blood flow through the apical conduit.…”
mentioning
confidence: 99%
“…More recently, Fragomeni et al used computational flow analysis to evaluate the systemic hemodynamic changes determined by a second outlet between the heart and the great vessels (i.e., from AVB), even in the context of mixed aortic valve disease. 17 The authors concluded that even under conditions of moderate AI, ''. The remaining antegrade flow (through the native aortic valve) after [AVB] supports, almost exclusively, cerebral perfusion, whereas the remaining body vessels perfuse by blood flow through the apical conduit.…”
mentioning
confidence: 99%
“…I read with great interest the paper by Fragomeni et al [1], in which they evaluated, by computational analysis, the effect of the severity of aortic regurgitation on cerebral perfusion in the setting of apicoaortic conduit (AAC). They showed that perfusion of epiaortic vessels after AAC, in cases of mixed aortic valve disease, was achieved by blood flow through the native aortic valve.…”
mentioning
confidence: 99%